2015
DOI: 10.1590/s0100-204x2015001200010
|View full text |Cite
|
Sign up to set email alerts
|

Forage potential and silage quality of four varieties of saccharine sorghum

Abstract: -The objective of this work was to evaluate four cultivars of saccharine sorghum (Sorghum bicolor) regarding productivity, chemical composition of plant parts, and quality of the ensiling process. The tested varieties of saccharine sorghum were BRS 506, BRS 508, BRS 509, and BRS 511. The experiment was divided into two trials, which assessed: production, morphological composition, and nutritional quality of the saccharine varieties; and fermentation quality and nutritional value of the silage produced from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
(20 reference statements)
2
10
0
Order By: Relevance
“…Studies on the use of grain sorghum for silage production are scare in Brazil. Forage sorghum cultivars, such as BRS 610 and BRS 655, have been studied for agronomic characteristics, chemical composition, and digestibility (Machado et al, 2012;Albuquerque et al, 2013;Santos et al, 2013), as have some cultivars of sweet sorghum, such as BRS 506 (Gomes et al, 2006;Orrico Junior et al, 2015). However, evaluations of nitrogen and carbohydrates fractions, as well as kinetics parameters are rare in sorghum silage evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the use of grain sorghum for silage production are scare in Brazil. Forage sorghum cultivars, such as BRS 610 and BRS 655, have been studied for agronomic characteristics, chemical composition, and digestibility (Machado et al, 2012;Albuquerque et al, 2013;Santos et al, 2013), as have some cultivars of sweet sorghum, such as BRS 506 (Gomes et al, 2006;Orrico Junior et al, 2015). However, evaluations of nitrogen and carbohydrates fractions, as well as kinetics parameters are rare in sorghum silage evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…The fact no differences were found between the intake and performance of animals fed saccharine or forage sorghum silages stands out. The low grain production of saccharine sorghum (Orrico Junior et al, 2015) is offset by the high content of soluble sugars (Neto et al, 2017), resulting in silage with a nutritional value similar to that of the traditionally used sorghum silage. Therefore, BRS 506 and BRS 511, saccharine sorghum varieties, can be used in ruminant feed.…”
Section: Resultsmentioning
confidence: 99%
“…Despite being researched for the production of sugar and alcohol, few studies use saccharin varieties as bulky sources for feeding ruminants. Orrico Junior et al (2015) evaluated the forage potential of four varieties of sorghum in terms of plant and silage productivity, botanical composition, and nutritional value. According to these authors, plants of this species can reach dry matter yield of 24 Mg ha -1 , average crude protein contents of 5%, and in vitro dry matter digestibility coefficient of up to 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Saccharine sorghum (Sorghum bicolor (L.) Moench) was improved to be used in ethanol production, mainly during the sugarcane off-season (De Nóbile & Nunes, 2014), because it is a bioenergetic species whose culm is rich in fermentable sugars (Anandan, Zoltan, Khan, Ravi, & Blümmel, 2012;Orrico Junior et al, 2015). In addition, this species resembles sugarcane plants due to a rapid productive cycle, mechanisable harvest, succulent culms and good bagasse production (Parrella, 2011), which can be used for bioenergy production and as animal feed (De Nóbile & Nunes, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The silage offered to animals can affect the quality of their final products, such as milk and meat (Campos et al, 2017;Milewski et al, 2014), denoting the importance of studies that investigate the diet effects (Holanda Júnior, 2006;Manarelli et al, 2019;Pereira et al, 2016). Considering that other studies (Manarelli et al, 2019;Orrico Junior et al, 2015) found variations in the effect of 'BRS506' saccharin sorghum silage on animal performance and carcass characteristics, it is important to evaluate the quality parameters of meat of sheep fed with this silage.…”
Section: Introductionmentioning
confidence: 99%